Hydrogen gas (H2) delivered by intraperitoneal injection alleviated methionine- and choline-deficient diet-induced metabolic dysfunction–associated steatotic liver disease in mice via inhibiting GSDMD- and GSDME-mediated pyroptosis - Chen, Yun; Wang, Kangrong; Guo, Wenhai; Lu, Chengqin; Suo, Wenting; Li, Qiuling; Deng, Yao; Chen, Xinling; Dai, Min; Zhang, Xiaodong; Xu, Jiean; Su, Wen; et al. (Frontiers in Pharmacology, 2025)
BackgroundHydrogen gas (H2), which is the lightest and diffusible gas molecule, has strong abilities to alleviate excessive oxidative stress, inflammation, and apoptosis. Inhalation of H2 is beneficial for preventing the damage of the lung, heart, brain, liver, kidneys, and many other organs. However, the effect of intraperitoneal injection of H2 on metabolic dysfunction–associated steatotic liver disease (MASLD) is unclear.ObjectiveThe aim of this study is to investigate whether intraperitoneal injection of H2 can improve MASLD, and if so, what are the key innate immune mechanisms involved?MethodsThe MASLD mouse model was established by feeding a methionine- and choline-deficient (MCD) diet for 3 weeks. H2 was daily given by intraperitoneal injection since the eighth day of MCD diet feeding, and lasted for 2 weeks. Serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were examined to evaluate liver injury. Hematoxylin and eosin (H&E) staining, Oil Red O staining, qPCR analysis of hepatic lipid metabolism genes, and detection of hepatic triglyceride (TG) levels were performed to evaluate hepatic steatosis. Masson trichrome staining and Collagen-I and Collagen-III protein levels were used to evaluate liver fibrosis. The liver 3-nitrotyrosine (3-NT) was detected by immunoblotting and immunofluorescence, and the levels of malondialdehyde (MDA) and reduced glutathione (GSH) were measured using kits to evaluate redox homeostasis. The activation of TLR4-mediated innate immune signaling and pyroptosis were tested by immunoblotting and immunofluorescence. Moreover, hepatic protective effect and anti-pyroptosis effect of H2 were further confirmed by H2-rich DMEM-treated HepG2 cells in vitro.ResultsSupplementing with H2 by intraperitoneal injection protected MCD diet-fed mice against hepatic steatosis and fibrosis by down-regulating de novo lipogenesis and fatty acid uptake genes, as well as hepatic Collagen-Ⅰ and Collagen-Ⅲ protein levels, while up-regulating lipid export genes. Mechanistically, H2 modulated hepatic redox homeostasis by suppressing 3-NT and MDA levels, while increasing the reduced GSH levels. Subsequently, reactive oxygen species (ROS)-related innate immune signaling, including the expression of TLR4, and the activation of NF-κB, ERK1/2, p38 MAPK, and JNK in the liver, were all inhibited by H2 treatment. These further contributed to inhibiting the expression of TNF-α, IL-1β, and IL-18 in the liver. The maturation of IL-1β and IL-18, the full-length of the classical pyroptosis trigger GSDMD, and the cleavage of GSDMD processed by Caspase-1 in NLRP3 inflammasome (including NLRP3, ASC, Caspase-1) were all blocked by H2. In addition, H2 decreased both the full-length and cleaved forms of Caspase-11, Caspase-8, Caspase-3 and GSDME, and thus inhibiting the non-canonical pyroptosis signaling in the liver of MASLD mice. The anti-pyroptosis effects of H2in vitro were further confirmed by the reduced expression of inflammatory cytokines, the decreased full-length and cleaved forms of GSDMD and GSDME, and the reduced number of HepG2 cells with pyroptotic morphology.ConclusionH2 is an anti-pyroptosis gas molecule, intraperitoneal injection of H2 is a novel therapeutic strategy for MASLD that deserves further investigation.